Business challenges and strategies for development of Small- and Medium-sized Enterprises (SMEs) in Malaysia - Ahmad, S.; Abdul Rani, Nazatul Shima; Mohd Kassim, S. (Inderscience Publication, 2010)
Despite their significant role in both the developed and the developing economies, Small-and Medium-sized Enterprises (SMEs) are faced with the greater risk of business failure with past statistics indicating that over half of all new ventures will not enjoy long-term success. They face varioustypes of difficulties and business challenges. This paper attempts to examine the issues, and explain how the business owners of SMEs in Malaysia strategise their operation to overcome the failure. The study highlighted several challenges faced by the firms, and to overcome these issues, SMEs havefollowed numerous strategies. The study revealed that business success is a result of implementing a mix of business, operation and management strategies. The paper concludes with the possible remedies, recommendations and future enhancements.